Eye-Tracking Analysis of Attention to an Electronic Storybook for Minimally Verbal Children With Autism Spectrum Disorder. (May 2019) - Thompson, Julie L.; Plavnick, Joshua B.; Skibbe, Lori E.
E-books may be particularly useful for differentiating instruction across a wide range of learners including those with autism spectrum disorder who are minimally verbal (MV-ASD). But the extent to which children with MV-ASD benefit from e-book instruction is unknown. Using eye-tracking equipment and software, we measured the duration of attention to print and pictures when presented with an e-book of 10 elementary-aged prereading children with MV-ASD and five prereading children with typical development. Furthermore, we analyzed eye-gaze duration, left-to-right gaze, and point-to-point correspondence from word to picture across different e-book stimuli (e.g., highlighting text, read-aloud). Results indicated different duration of attending to pictures and print between typically developing children and children with ASD. Although there were some indications that differing stimuli may influence attention to salient e-book components, most notable was that children with MV-ASD attended very little to literacy concepts within the e-book.